The application of accounting prudence on upper tone management (UTM) of publicly listed service companies in the Philippines through the interpretation of financial profitability and management discussion & analysis (MD&A) - Feliciano, Seth Rafael V. (Animo Repository, 2023)
This study determined how accounting prudence is related to the use of tone management by those holding managerial positions within a company. An analysis using profitability ratios and the Management Discussion & Analysis (MD&A) portion of the SEC 17-A filings for the fiscal years 2017 to 2021 was conducted. The researchers hypothesized that prudence limits the ability of manager opportunism in relation to the tone used in qualitative disclosures particularly, the increased requirements in the recognition of profits to have an impact on the reported profitability. In order to determine the moderating effect of the profitability ratios, the researchers utilized Panel Data Regression and used word sentiment analysis to the MD&A of thirty-nine (39) publicly listed service companies in the Philippines. Focused on whether or not the moderating variables Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM), along with Accounting Prudence, (independent variable) manipulate TONE, specifically its residual, Upper Tone Management (UTM), proxy of which is Abnormal Tone (ABTONE), and TONE’s predicted value, Normal Tone (NORMTONE), the results show a significant relationship to a circumstantial extent. Results of the sentiment word analysis present companies' disclosure leaning more on negative words. Furthermore, it was discovered that OPM with SKEW and CSCORE are significant to ABTONE, entailing an effect on tone management. However, OPM with CSCORE and CRATIO along with GPM and NPM, showed significance to NORMTONE. The results and findings of the research were beneficial to shareholders and investors, firm management and board of directors (BoD), regulatory bodies, as well as the academe and future researchers.